SYSTEMES D’INFORMATION GEOGRAPHIQUE (SIG), DÉVELOPPEMENT ET COMPÉTITIVITÉ TERRITORIALE : QUELLE ARTICULATION ? - CAS DE LA VILLE DE MARRAKECH - - EL BAKKARI, Mohamed (Studia Universitatis Babeș-Bolyai Geographia, 2021)
Geographical Information Systems (GIS), Development and Territorial Competitiveness: What Connection? The Case of the City of Marrakech. Marrakech is a city in search of an urban balance in social, economic and environmental terms. This balance traces the reflection of a political and economic ideal of a new and smart city, which essentially instrumentalizes a well-studied basic urban policy, inspiring confidence. The birth of a new urban concept for Marrakech is initiated by an urban will, as part of a vision of sustainable and equitable territorial development. The GIS, as a means of territorial management and decision-making in terms of spatial planning and control, has emerged in urban management strategies, following the evolution of the territory and the changes that occurred, in addition to the current circumstances regarding climate change, urban transformations and globalization. GIS is therefore a consequence of this evolution, which is also experienced by the city of Marrakech. The connection between GIS and territory leads to relevant results for spatial organization, given the ingrained adoption of information techniques at the level of municipalities and between municipalities. In this context, this paper approaches the insertion of new technologies to assist the decision-making process by territorial actors and the digitization of spatial data for a rational urban planning.